Mechanical properties and microstructural analysis of friction stir processed AA6056-zirconium dioxide (ZrO2). (2021) - Sathish, T.; Muthu, G.; Vijayakumar, M.D.; Dhinakaran, V.; Ram, P.M. Bupathi
Abstract: In this experimental investigation intended on to fabricate the aluminium alloy AA6056 with adding together of Zirconium dioxide through Friction stir processing route. The Friction stir processing is a similar way of friction stir welding process, it is forced out to mixing the Zirconium dioxide into AA6056 while in FSP. The parameters of FSP are tool speed (800, 1000, 1200 and 1400 rpm), transverse speed (60 mm/min) and tool axial force (5 kN). The mechanical properties of tensile strength are measured for the four different specimens, produced with different rotational speed. The micro hardness is measured repeatedly on the joint area and base material zone with the help of Vickers hardness tester machine. Excellent hardness values are observed in the FSP zone compare to other zones; it tells about the FSP was carried out effectively. The SEM image of the tensile specimens for it in broken area was analyzed by the way of 3D profilometry images.